Inherited platelet dysfunction and hematopoietic transcription factor mutations - Natthapol Songdej; A. Koneti Rao (Platelets, 2017)
Transcription factors (TFs) are proteins that bind to specific DNA sequences and regulate expression of genes. The molecular and genetic mechanisms in most patients with inherited platelet dysfunction are unknown. There is now increasing evidence that mutations in hematopoietic TFs are an important underlying cause for the defects in platelet production, morphology, and function. The hematopoietic TFs implicated in the patients with impaired platelet function include Runt related TF 1 (RUNX1), Fli-1 proto-oncogene, ETS TF (FLI1), GATA-binding protein 1 (GATA1), and growth factor independent 1B transcriptional repressor (GFI1B). These TFs act in a combinatorial manner to bind sequence-specific DNA within a promoter region to regulate lineage-specific gene expression, either as activators or as repressors. TF mutations induce rippling downstream effects by simultaneously altering the expression of multiple genes. Mutations involving these TFs affect diverse aspects of megakaryocyte biology and platelet production and function, culminating in thrombocytopenia, platelet dysfunction, and associated clinical features. Mutations in TFs may occur more frequently in the patients with inherited platelet dysfunction than generally appreciated. This review focuses on the alterations in hematopoietic TFs in the pathobiology of inherited platelet dysfunction.